Implementasi Privacy-Preserving Record Linkage untuk Meningkatkan Manajemen Hubungan Pelanggan: Studi Kasus pada Perusahaan Manufaktur di Indonesia - Muhamad Ikbal; Achmad Nizar Hidayanto; Ni Wayan Trisnawaty; R. Yugo Kartono Isal (AI Society & STMIK Indonesia, 2025)
As cross-organizational collaboration increases, balancing data utility with privacy protection becomes essential. This study addresses the challenge by implementing Privacy-Preserving Record Linkage (PPRL) using a deterministic hashing approach at an Indonesian manufacturing firm and a leasing company. The system employs a dual-layer hashing technique (MD5 followed by salted SHA-256) to securely link standardized identifiers without revealing raw personal data. The objective was to enhance Customer Relationship Management (CRM) by identifying shared customers for targeted outreach. The approach yielded 2.6 million matched records out of over 36 million, enabling the leasing firm to achieve a 2-4% conversion rate through personalized campaigns. Results demonstrate high efficiency, scalability, and compliance with Indonesia’s data protection law, offering a replicable framework for privacy-conscious data integration in regulated environments.